Yeast Expression Systems: Overview and Recent Advances - Baghban, Roghayyeh; Farajnia, Safar; Rajabibazl, Masoumeh; Ghasemi, Younes; Mafi, AmirAli; Hoseinpoor, Reyhaneh; Rahbarnia, Leila; Aria, Maryam (Molecular biotechnology, 2019)
Yeasts are outstanding hosts for the production of functional recombinant proteins with industrial or medical applications. Great attention has been emerged on yeast due to the inherent advantages and new developments in this host cell. For the production of each specific product, the most appropriate expression system should be identified and optimized both on the genetic and fermentation levels, considering the features of the host, vector and expression strategies. Currently, several new systems are commercially available; some of them are private and need licensing. The potential for secretory expression of heterologous proteins in yeast proposed this system as a candidate for the production of complex eukaryotic proteins. The common yeast expression hosts used for recombinant proteins’ expression include Saccharomyces cerevisiae, Pichia pastoris, Hansenula polymorpha, Yarrowia lipolytica, Arxula adeninivorans, Kluyveromyces lactis , and Schizosaccharomyces pombe . This review is dedicated to discuss on significant characteristics of the most common methylotrophic and non-methylotrophic yeast expression systems with an emphasis on their advantages and new developments.